Impact and Sensitivity Analysis of Soil Water and Heat Transfer Parameterizations in Community Land Surface Model on the Tibetan Plateau. (12th September 2021) - Deng, Mingshan; Meng, Xianhong; Lu, Yaqiong; Li, Zhaoguo; Zhao, Lin; Hu, Zeyong; Chen, Hao; Shang, Lunyu; Wang, Shaoying; Li, Qian
Abstract: Soil water and heat transfer is especially complicated during the freezing and thawing processes over the high‐altitude cold regions. In this study, four sensitivity tests of soil water and heat transfer parameterizations including replacing soil property data (SP1), soil resistance scheme modification (SP2), soil thermal conductivity scheme (SP3) and virtual temperature scheme (SP4), and four combination experiments (SP1+SP2+SP3/SP5, SP1+SP2+SP4/SP6, SP1+SP3+SP4/SP7, and SP1+SP2+SP3+SP4/SP8) were done using Community Land Model (CLM5.0) to examine its performances for soil water and heat transfer modeling on the Tibetan Plateau (TP) both in single‐point and regional simulations. The observed data from five eddy covariance sites, four soil moisture and temperature networks and 60 sites of soil temperature observations on the TP were used to evaluate the results. Single‐point simulations show that SP2 experiment reduced the wet biases of soil moisture in semiarid area, but enhanced the error of soil temperature. SP6 shows the best performances in simulating soil moisture, and SP3 in soil temperature. Regional simulations show that the SP7 experiment had the best performances for soil water and heat transfer simulation on the TP, and improved the simulation of soil freezing‐thawing processes. Compared to CLM5.0 default simulation, SP7 shows the best performances. For soil moisture, it reduced average Bias by 23%, Root Mean Square Error (RMSE) by 18%, and increased the Correlation Coefficient (Corr) by2%. For soil temperature, it reduced the Bias by 9%, 10%, 23%, and 13% at four soil depths on the TP, respectively. Plain Language Summary: Soil water and heat transfer is a critical feature of the land surface process. Variations in soil water and heat transfer are important for water and energy partition between atmosphere and land surface. In this study, single‐point simulations were evaluated against the observed soil moisture and temperature and surface heat flux in different climate zones over the Tibetan Plateau (TP). Single‐point results using Community Land Model (CLM5.0) show that the simulated soil temperature generally coincided with observations, and large biases for soil moisture still remain in cold region. By replacing the soil property data in CLM5.0 default, simulations of soil moisture and temperature were improved during thawing period. To reduce the biases, modification of soil parameterization in CLM5.0 are proposed, (a) setup soil resistance to 0 in soil evaporation, (b) replacing freezing temperature by virtual temperature to determine occurring of phase change, (c) Using Balland and Arp schemes in soil thermal conductivity. We use different combinations of the above modifications to do the sensitivity experiments. The observed data from five eddy covariance sites, four soil moisture and temperature networks and 60 sites of soil temperature observations on the TP were used to evaluate the results. Regional simulations show that after modifying soil property data, the combination using Balland and Arp scheme and the virtual temperature scheme had the best performances for soil water and heat transfer simulation on the TP, reduced the wet biases from the beginning of melting stage. Key Points: Simulation biases are evident in soil water and heat transfer After modifying the dry surface layer, it improves soil moisture simulation in semiarid area Use of Balland and Arp scheme and virtual temperature scheme improves the simulations of soil water and heat transfer